Egzotyzmy w "Ognistym aniele" Walerego Briusowa = Exoticisms in "The Fiery Angel" by Valery Bryusov - Gajda, Radosław (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
On the pages of the novel exotic loanwords were used to create the colour of the epoch and to depict its meaning. The exotic loanwords in "The Fiery Angel" assume the importance of symbols; this effect is achieved by Briusow mainly through dynamics, symbolism and metaphors. In Briusow's novel, within limited space-time continuum, the exotic loanwords become definitely the most important means of artistic expression.
Keywords: Briusow, Walery Jakowlewicz (pisarz rosyjski; 1873-1924); symbolizm; literatura rosyjska; 20 w.